2013
DOI: 10.1021/jz401649a
|View full text |Cite
|
Sign up to set email alerts
|

Conductance Switching and Many-Valued Logic in Porphyrin Assemblies

Abstract: We investigate quantum interference in the transport properties of porphyrinbased molecular devices, and are able to develop a minimal but qualitatively accurate model of conductance based on the maximally localized Wannier functions of just the isolated molecule. We find that transmission at or near the Fermi level can be engineered to vary by orders of magnitude in response to hydrogen tautomerization in the inner ring, a recently developed experimental capability. This allows us to suggest that tape porphyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Conversely, we believe that perturbing the electronic properties of molecular tautomers (in our case by adding two more H atoms), without any change of their orientation, represents a reasonable alternative in the development of new devices based on molecular tautomers. However, starting from an ordered array of tautomers, it could even be possible to switch the hydrogen atoms alignment of a porphyrin domain by flowing an in‐plane current along the molecular pathways if the current is tuned at a frequency that maximizes energy transfer to that of the N–H vibration .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, we believe that perturbing the electronic properties of molecular tautomers (in our case by adding two more H atoms), without any change of their orientation, represents a reasonable alternative in the development of new devices based on molecular tautomers. However, starting from an ordered array of tautomers, it could even be possible to switch the hydrogen atoms alignment of a porphyrin domain by flowing an in‐plane current along the molecular pathways if the current is tuned at a frequency that maximizes energy transfer to that of the N–H vibration .…”
Section: Resultsmentioning
confidence: 99%
“…80) on the control of the scaffold structural freedom by means of surface anchoring 81,83 or molecular assembling. 82,84 Finally, let us mention a recent work where the third law of thermodynamics is investigated for a 1D model boron rotor B 13 + . 55 In ref.…”
Section: Discussionmentioning
confidence: 99%
“…Besides metallic electrodes, molecules with a small HOMO–LUMO gap are also necessary, aiming to reduce the energy separation between the FMOs and the Fermi level of the electrodes. Porphyrin, well-known for its small HOMO–LUMO gap, rigid π-conjugated structure and unique light harvesting properties, is an excellent candidate for nanoelectronic and photovoltaic devices. Recently, through dehydrogenation reaction, He et al demonstrated that porphines can be steered toward the graphene edges forming C–C covalent bonds, thus providing an avenue to construct graphene-porphine-graphene (GPG) molecular junctions . Motivated by this work, here we theoretically investigate the electronic transport properties of porphine bridged between two semi-infinite graphene electrodes by employing the nonequilibrium Green’s function formalism combined with density functional theory (that is, the so-called NEGF+DFT approach).…”
Section: Introductionmentioning
confidence: 99%